ANALYSIS OF WORK BEHAVIOR OF HUNTAP FACILITATORS FROM THE THEORY PLANNED BEHAVIOR (TPB) AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PERSPECTIVES - Fauzan, Muhammad; Idris, Azis; Adda, Harnida Wahyuni (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
This research aims to analyze the work behavior of the facilitators from the perspective of Planned Behavior Theory (TPB) and Organizational Citizenship Behavior (OCB). This research paradigm is postpositivistic with a qualitative approach. Data were collected through interviews with seven informants, namely the Regional Coordinator, Senior Facilitator, Technical Facilitator, Economic Facilitator and Social Facilitator. The data analysis technique used was the triangulation method using NVIVO 12 analysis software. The results showed that the work behavior of the facilitators from the perspective of planned behavior theory (TPB), facilitators have a responsibility to help fellow humans. Many facilitators see this role as an opportunity to provide support and solutions for those affected by the disaster. A high sense of caring is also the main goal of the informants in carrying out their duties as facilitators. From the perspective of Organizational Citizenship Behavior (OCB), facilitators have a tendency to help fellow colleagues as part of teamwork if they are absent, but with some considerations. The work as a facilitator is not bound by time and place, so it is more flexible.